The metabolic equivalent of task score: a useful metric for comparing high-functioning hip arthroplasty patients - Thomas C. Edwards; Brogan Guest; Amy Garner; Kartik Logishetty; Alexander D. Liddle; Justin P. Cobb (Bone & Joint Research, 2022)
Aims: This study investigates the use of the metabolic equivalent of task (MET) score in a young hip arthroplasty population, and its ability to capture additional benefit beyond the ceiling effect of conventional patient-reported outcome measures. Methods: From our electronic database of 751 hip arthroplasty procedures, 221 patients were included. Patients were excluded if they had revision surgery, an alternative hip procedure, or incomplete data either preoperatively or at one-year follow-up. Included patients had a mean age of 59.4 years (SD 11.3) and 54.3% were male, incorporating 117 primary total hip and 104 hip resurfacing arthroplasty operations. Oxford Hip Score (OHS), EuroQol five-dimension questionnaire (EQ-5D), and the MET were recorded preoperatively and at one-year follow-up. The distribution was examined reporting the presence of ceiling and floor effects. Validity was assessed correlating the MET with the other scores using Spearman’s rank correlation coefficient and determining responsiveness. A subgroup of 92 patients scoring 48/48 on the OHS were analyzed by age, sex, BMI, and preoperative MET using the other metrics to determine if differences could be established despite scoring identically on the OHS. Results: Postoperatively the OHS and EQ-5D demonstrate considerable negatively skewed distributions with ceiling effects of 41.6% and 53.8%, respectively. The MET was normally distributed postoperatively with no relevant ceiling effect. Weak-to-moderate significant correlations were found between the MET and the other two metrics. In the 48/48 subgroup, no differences were found comparing groups with the EQ-5D, however significantly higher mean MET scores were demonstrated for patients aged < 60 years (12.7 (SD 4.7) vs 10.6 (SD 2.4), p = 0.008), male patients (12.5 (SD 4.5) vs 10.8 (SD 2.8), p = 0.024), and those with preoperative MET scores > 6 (12.6 (SD 4.2) vs 11.0 (SD 3.3), p = 0.040). Conclusion: The MET is normally distributed in patients following hip arthroplasty, recording levels of activity which are undetectable using the OHS. Cite this article: Bone Joint Res 2022;11(5):317–326.